Nursing intervention in front of hemodialysis patients - Almeida, Roberta Graziella Pereira da Costa Araújo de (2023)
Objective: Identify the nursing interventions provided to patients undergoing hemodialysis. Method: This is an integrative review article carried out through the analysis of 10 scientific articles Portal da Biblioteca Virtual em Saúde (VHL), in the databases Latin American Caribbean Literature in Health Sciences (LILACS) and Electronic Library Base de Nursing Data (BDENF) and Scientific Electronic Library Online (SCIELO). Results: The nurse is responsible for evaluating and maintaining hemodialysis accesses, interpreting laboratory tests and also for making decisions together with the medical team, in addition to to be able to prevent, identify and treat complications presented by patients before, during and after the procedure. Conclusion: In short, this research is important because it provides subsidies, makes the team responsible for hemodialysis aware, evaluates the needs and importance of the patient's quality of life, in undergoing hemodialysis and provides them with optimized methods of this form of treatment.